Inter-specific hybridization and its potential for aquaculture of fin fishes - Rahman, Md. Aminur; Arshad, Aziz; Marimuthu, Kasi; Ara, Roushon; Nurul Amin, Sarker Mohammad (Academic Journals, 2013)
Inter-specific hybrids have been produced to increase growth rate, improve productivity through hybrid vigor, transfer desirable traits, reduce unwanted reproduction through production of sterile fish, combine other valuable traits such as good flesh quality, disease resistance and increase environmental tolerances, better food conversion, take advantages of sexual dimorphism and increase harvesting rate in culture systems. Hybrids play a significant role for increase in aquaculture production of several species of freshwater and marine fishes; for example, hybrid catfish in Thailand, hybrid stripped bass in the USA, hybrid tilapia in Israel and hybrid characids in Venezuela. Despite its’ wide-spread use in aquaculture, there have been an impression that hybrids do not hold much attraction for aquaculturist. With the expansion of aquaculture sector and the increased number of species being bred and farmed, there are hybrids that now account for a substantial proportion of national aquaculture production and other hybrids may be emerging through further development. As the domestication of fish species increases, the possibilities to increase production through appropriate hybridization techniques is ongoing with a view to produce new hybrid fishes, especially in culture systems where sterile fish may be preferred because of the concern that fish may escape into the open freshwater, marine and coastal environment. Chromosome-set manipulation (polyploidization) has been combined with hybridization to increase the viability and to improve developmental stability of hybrid fishes. Intentional or accidental hybridization can lead to unexpected and undesirable results in hybrid progeny, such as reduced viability and growth performances, loss of color pattern and flesh quality and also raises risks to maintenance of genetic integrity of species if the hybrids escape to the natural habitat and undergo backcrosses with the parental species. The success of inter-specific hybridization can be variable and depend on the genetic structure, crossing patterns, gamete compatibility and gene flow patterns of the parental species. Appropriate knowledge on the genetic constitution of the broodstock, proper broodstock management and monitoring of the viability and fertility of the progeny of brood fishes is thus very crucial before initiating hybridization experiments. In addition, some non-generic factors such as weather conditions, culture systems, seasons and stresses associated with selecting, collecting, handling, breeding and rearing of broodstock and progeny may greatly influence hybridization success in a wide variety of freshwater and marine fin fishes.